Managerial Compensation and the Market Reaction to Bank Loans - Almazan, Andres; Suarez, Javier (Review of Financial Studies, 2003)
This article considers why a manager would choose to submit himself to the discipline of bank monitoring. This issue is analyzed within the context of a model where the manager enjoys private benefits, which can be restricted by the monitor, and is optimally compensated by shareholders. Within this setting we find that managers will submit to monitoring when they receive favorable private information. This result is consistent with event study evidence that suggests that the market has a favorable view of financing choices that increase monitoring.